Pulmonary artery perfusion versus no pulmonary perfusion during cardiopulmonary bypass in patients with COPD: a randomised clinical trial. Issue 1 (6th September 2016) - Buggeskov, Katrine B; Sundskard, Martin M; Jonassen, Thomas; Andersen, Lars W; Secher, Niels H; Ravn, Hanne B; Steinbrüchel, Daniel A; Jakobsen, Janus C; Wetterslev, Jørn
Abstract : Introduction: Absence of pulmonary perfusion during cardiopulmonary bypass (CPB) may be associated with reduced postoperative oxygenation. Effects of active pulmonary artery perfusion were explored in patients with chronic obstructive pulmonary disease (COPD) undergoing cardiac surgery. Methods: 90 patients were randomised to receive pulmonary artery perfusion during CPB with either oxygenated blood (n=30) or histidine-tryptophan-ketoglutarate (HTK) solution (n=29) compared with no pulmonary perfusion (n=31). The coprimary outcomes were the inverse oxygenation index compared at 21 hours after starting CPB and longitudinally in a mixed-effects model (MEM). Secondary outcomes were tracheal intubation time, serious adverse events, mortality, days alive outside the intensive care unit (ICU) and outside the hospital. Results: 21 hours after starting CPB patients receiving pulmonary artery perfusion with normothermic oxygenated blood had a higher oxygenation index compared with no pulmonary perfusion (mean difference (MD) 0.94; 95% CI 0.05 to 1.83; p=0.04). The blood group had also a higher oxygenation index both longitudinally (MEM, p=0.009) and at 21 hours (MD 0.99; CI 0.29 to 1.69; p=0.007) compared with the HTK group. The latest result corresponds to a difference in the arterial partial pressure of oxygen of 23 mm Hg with a median fraction of inspired oxygen of 0.32. Yet the blood or HTK groups did not demonstrate a longitudinally higher oxygenation index compared with no pulmonary perfusion (MEM, p=0.57 and 0.17). Similarly, at 21 hours there was no difference in the oxygenation index between the HTK group and those no pulmonary perfusion (MD 0.06; 95% CI −0.73 to 0.86; p=0.87). There were no statistical significant differences between the groups for the secondary outcomes. Discussion: Pulmonary artery perfusion with normothermic oxygenated blood during cardiopulmonary bypass appears to improve postoperative oxygenation in patients with COPD undergoing cardiac surgery. Pulmonary artery perfusion with hypothermic HTK solution does not seem to improve postoperative oxygenation. Trial registration number: NCT01614951; Pre-results.